O processo de mediação em arquivos pessoais: o caso do Instituto Evandro Chagas Belém/PA 2018 - MONTEIRO, Natália de Paula Souza (2021)
Analysis of the process of information mediation in the treatment of personal files of the Evandro Chagas Institute (ECI) from the perspective of Postmodern Archival Science, taking into account the professional's abilities and knowledge to mediate the information contained in the collection and considering that personal files have specificity that differentiate them from the archives of collective entities. We sought in the archival literature the theoretical contributions about information mediation and personal files and, to complement the discussions on the subjects addressed, a brief approach was needed on Postmodern Archival Science, organic information and informational literacy. The research is characterized as descriptive, with an interview with the IEC archivist as a tool for data collection. With the analysis of the interview, it was realized that, in fact, mediation is a process and it also applies in the treatment of information in personal files.